IMPLEMENTATION OF E-COURT ASSEMBLY APPLICATION IN THE HANDLING OF THE CRIMINAL ACTION OF MURDER - Dwi Putri Melati; Elti Yunani; Januri Januri (Proceedings of the 1st International Conference on Social Science (ICSS), 2023)
An electronic trial (e-court) is a court process carried out with the support of information and communication technology, audio-visual and other electronic means. This study aims to find out about the implementation of the e-court trial in handling the crime of murder and the inhibiting factors in the e-court trial process in the handling of the crime of murder. This research is normative legal research by applying two approaches, namely the empirical juridical approach and the normative juridical approach. The results of this study indicate that the implementation of the e-court trial in handling the crime of murder is carried out by examining the summons and preparing the facilities and infrastructure needed during the e-court trial (online). The inhibiting factors in the e-court trial process in handling the crime of murder include: evidence, the difficulty of presenting witnesses, and inadequate human resources, inadequate facilities and infrastructure